2017
DOI: 10.1039/c7ce00909g
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up approach for the preparation of hybrid nanosheets based on coordination polymers made of metal–diethyloxaloacetate complexes linked by 4,4′-bipyridine

Abstract: [M(deox)2(bpy)]∞ precipitated as nanosheets arranged in different morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For hybrid coordination polymers, several examples of this morphology have already been observed in samples obtained by solvothermal , and supercritical crystallization techniques. The recovered sample at 20 h was mainly crystalline (Figure b).…”
Section: Resultsmentioning
confidence: 81%
“…For hybrid coordination polymers, several examples of this morphology have already been observed in samples obtained by solvothermal , and supercritical crystallization techniques. The recovered sample at 20 h was mainly crystalline (Figure b).…”
Section: Resultsmentioning
confidence: 81%
“…scCO 2 has been traditionally used for removing entrapped solvents within MOF structures. However, in the past few years, it has also been used in our research group as a solvent for the synthesis of MOFs, either by using exclusively scCO 2 , or adding a cosolvent, with interesting applications in medicine (bioMOFs), sensors or gas adsorption after hybridizing with graphene aerogels . In essence, the use of the scCO 2 technology has proved excellent to prepare materials for biomedical applications .…”
Section: Introductionmentioning
confidence: 99%
“…This axiom is applied in this work, since the designed synthetic processes avoid the use of solvothermal techniques and high-boiling-point solvents. Previous publications had shown that a series of bipyridyl CPs can be easily prepared by using greener techniques. …”
Section: Introductionmentioning
confidence: 99%